A quantitative and qualitative evaluation of LISA, a decision support system for chemotherapy dosing in childhood acute lymphoblastic leukaemia - Bury, Jonathan; Hurt, Chris; Roy, Anindita; Bradburn, Mike; Cross, Simon; Fox, John; Saha, Vaskar (Studies in health technology and informatics, 2004)
To assess the acceptability to clinicians of a web-based decision support system designed to assist with dosage adjustments during maintenance therapy for childhood Acute Lymphoblastic Leukaemia (ALL), and to evaluate the potential impact of the system on decision-making and dosage calculations. Balanced-block crossover experiment with simulated cases; questionnaire study and semi-structured interviews. 36 clinicians with differing experience in the management of ALL. Subjects were asked to decide on appropriate levels of chemotherapy dosing for 8 simulated cases, 4 using the LISA decision support system, 4 using conventional paper-based records and guidance. Number of protocol-consistent dosage decisions made; time taken to manage each case; accuracy of dosage calculations; subjects' opinions as to whether or not they would use the system in practice. ADDITIONAL OUTCOME MEASURES: Functions subjects would like to see in an idealised system; subjects' satisfaction with the implementation of the functions provided by LISA; qualitative data on issues subjects felt would impact upon the successful deployment of the system.